Contribution of the perfusion technique in computed tomography and magnetic resonance imaging to the stroke diagnostic: a narrative review - Ferreira, Aida (2022)
Objective – To evaluate the utility of perfusion in computed tomography (CT) and magnetic resonance (MR) in the diagnosis of acute ischemic stroke. Methods – An electronic literature research was performed, looking for prospective studies, regarding an adult population at risk of cerebral ischemia with a diagnostic evaluation of perfusion studies, having perfusion sequences by CT (CPT) and MR (MRP) performed after a stroke. Of the 2,224 articles found, 28 matched the inclusion criteria for analysis of definitions (15 CT, 11 MRI, and 2 CT and MR). Furthermore, protocols and percentage levels of accuracy, sensitivity, and specificity were compared through metrics of frequency analysis and central expression. Results – In these articles, parameters and techniques for the acquisition of perfusion imaging either in CT or MRI were analyzed. Regarding it, was found that the accuracy, sensitivity, and specificity were 88.5%, 91.5%, and 90.5% for MRI and 83%, 86%, and 91.7% for CT, respectively. Conclusion – MRI remains the imaging method with greater clinical value, however, the CT study also presents as being an advantage, with better accessibility and rapidity, reducing the waiting time between the diagnosis and therapy.